Physiological responses of a rodent to heliox reveal constancy of evaporative water loss under perturbing environmental conditions - Cooper, Christine; Withers, P. (American Physiological Society, 2014)
Total evaporative water loss of endotherms is assumed to be determined essentially by biophysics, at least at temperatures below thermoneutrality, with evaporative water loss determined by the water vapor deficit between the animal and the ambient air. We present here evidence, based on the first measurements of evaporative water loss for a small mammal in heliox, that mammals may have a previously unappreciated ability to maintain acute constancy of total evaporative water loss under perturbing environmental conditions. Thermoregulatory responses of ash-grey mice (Pseudomys albocinereus) to heliox were as expected, with changes in metabolic rate, conductance, and respiratory ventilation consistent with maintaining constancy of body temperature under conditions of enhanced heat loss. However, evaporative water loss did not increase in heliox. This is despite our confirmation of the physical effect that heliox augments evaporation from nonliving surfaces, which should increase cutaneous water loss, and increases minute volume of live ash-grey mice in heliox to accommodate their elevated metabolic rate, which should increase respiratory water loss. Therefore, mice had not only a thermoregulatory but also a hygroregulatory response to heliox. We interpret these results as evidence that ash-grey mice can acutely control their evaporative water loss under perturbing environmental conditions and suggest that hygroregulation at and below thermoneutrality is an important aspect of the physiology of at least some small mammals.